Fundraising Strategi Dana Zakat Pada BAZNAS Kabupaten Banyumas - Imas Maelani Kamal; Yoiz Shofwa Shafrani (Profesional Muda Cendekia Publishing, 2022)
This article which aimed to find out any strategy used by BAZNAS in Banyumas Distric to gain zakat fund, and also analyze the threat during implement the fund raising strategies. The result of this study shows that BAZNAS of Banyumas Distric use direct and indirect method to raise zakat fund. The direct method of zakat fundraising in this study is by directly pick up the zakat fund from Muzakki, and enable the payment through QRIS (Quick Response Indonesian Standard). Then, indirect methode used by BAZNAS to gain zakat fund is by improving branding image of BAZNAS through direct promotions, events and scholarship to improve the Banyumas peoples’ awareness of the importance of paying Zakat. Artikel ini bertujuan untuk mengetahui strategi yang digunakan Badan Amil Zakat Nasional (BAZNAS) Kabupaten Banyumas dalam memperoleh dana zakat, serta mengetahui apa saja tantangan, dan hambatan selama pelaksanaan fundrising. Hasil penelitian ini menunjukkan dalam memperoleh dana zakat dari Muzakki, BAZNAS Kabupaten Banyumas menggunakan metode direct and indirect fundraising. Metode direct antara lain: jemput zakat dan pembayaran dengan QRIS. Adapun metode indirect antara lain: membuat branding kepada masyarakat untuk meningkatkan kesadaran masyarakat pada umumnya dan warga Kabupaten Banyumas secara khusus untuk membayar zakat.